Differences in anti-doping knowledge among Serbian professional athletes - Zoran Vesic; Jelena Stojicevic; Nemanja Rancic; Gorica Milovanovic; Jelena S. Rasic; Nenad Radivojevic; Nenad Radivojevic; Goran Prebeg; Dragan Atanasov; Milos Todorovic; Sonja Marjanovic; Milica Vukasinovic Vesic; et al. (Frontiers in Public Health)
ObjectivesThe aim of this study was to examine the impact of anti-doping education among professional athletes on anti-doping knowledge.MethodsA prospective cohort study was conducted on differences in knowledge toward doping among 404 professional athletes in relation to their education about doping.ResultsParticipants who underwent education answered correctly significantly more often on most of the questions compared to participants without education [difference of about 20–30% in the rate of correct answers is in favor of participants with education on every question; 8.49 (SD 2.75) vs. 11.04 (SD 1.89); p < 0.001]. The majority of participants in the group with prior education against doping answered 10 or more questions correctly out of a total of 13, while the group without prior education against doping most commonly had 7 to 11 correct answers (p < 0.001). The most significant predictors of correct answers are gender, number of years of training, type of sport (individual or team sport), and prior education about doping. The largest contribution to this model comes from the variable “prior education against doping,” followed by the type of sport.ConclusionOur research shows that prior anti-doping education is effective and has the essential contribution on athletes’ knowledge about doping.